The Eternal Night of Consumer Consciousness: The Metaphorical Embodiment of Darkness in Cormac McCarthy’s The Road - Inbar Kaminsky (European Journal of American Studies)
The essay strives to conceptualize the consumer consciousness of the father and the son in Cormac McCarthy’s The Road by maintaining that post-apocalyptic America has created a new socio-economic status of the non-consumer. The essay also explores the figurative role of the darkness in the novel in relation to the representation of corporeality of the characters and its role in the erosion of the father’s consumer consciousness. In addition, the essay discusses the broad significance of The Road as a post-9/11 novel and its thematic connection to Don DeLillo’s Falling Man.